Diurnal variations of BrONO₂ observed by MIPAS-B at midlatitudes and in the Arctic - Wetzel, Gerald; Oelhaf, Hermann; Höpfner, Michael; Friedl-Vallon, Felix; Ebersoldt, Andreas; Gulde, Thomas; Kazarski, Sebastian; Kirner, Oliver; Kleinert, Anne; Maucher, Guido; Nordmeyer, Hans; Orphal, Johannes; et al. (European Geosciences Union, 2017)
The first stratospheric measurements of the diurnal variation in the inorganic bromine (Bry) reservoir species BrONO2 around sunrise and sunset are reported. Arctic flights of the balloon-borne Michelson Interferometer for Passive Atmospheric Sounding (MIPAS-B) were carried out from Kiruna (68° N, Sweden) in January 2010 and March 2011 inside the stratospheric polar vortices where diurnal variations of BrONO2 around sunrise have been observed. High nighttime BrONO2 volume mixing ratios of up to 21 pptv (parts per trillion by volume) were detected in late winter 2011 in the absence of polar stratospheric clouds (PSCs). In contrast, the amount of measured BrONO2 was significantly lower in January 2010 due to low available NO2 amounts (for the build-up of BrONO2), the heterogeneous destruction of BrONO2 on PSC particles, and the gas-phase interaction of BrO (the source to form BrONO2) with ClO. A further balloon flight took place at midlatitudes from Timmins (49° N, Canada) in September 2014. Mean BrONO2 mixing ratios of 22 pptv were observed after sunset in the altitude region between 21 and 29 km. Measurements are compared and discussed with the results of a multi-year simulation performed with the chemistry climate model ECHAM5/MESSy Atmospheric Chemistry (EMAC). The calculated temporal variation in BrONO2 largely reproduces the balloon-borne observations. Using the nighttime simulated ratio between BrONO2 and Bry, the amount of Bry observed by MIPAS-B was estimated to be about 21–25 pptv in the lower stratosphere.